Insulin-like and IGF-like peptides in the silkmoth Bombyx mori: discovery, structure, secretion, and function - Mizoguchi, Akira; Okamoto, Naoki (Frontiers in Physiology, 2013)
A quarter of a century has passed since bombyxin, the first insulin-like peptide identified in insects, was discovered in the silkmoth Bombyx mori. During these years, bombyxin has been studied for its structure, genes, distribution, hemolymph titers, secretion control, as well as physiological functions, thereby stimulating a wide range of studies on insulin-like peptides in other insects. Moreover, recent studies have identified a new class of insulin family peptides, IGF-like peptides, in B. mori and Drosophila melanogaster, broadening the base of the research area of the insulin-related peptides in insects. In this review, we describe the achievements of the studies on insulin-like and IGF-like peptides mainly in B. mori with short histories of their discovery. Our emphasis is that bombyxins, secreted by the brain neurosecretory cells, regulate nutrient-dependent growth and metabolism, whereas the IGF-like peptides, secreted by the fat body and other peripheral tissues, regulate stage-dependent growth of tissues.